Transmission of epi-alleles with MET1-dependent dense methylation in Arabidopsis thaliana. - Michael Watson; Emily Hawkes; Peter Meyer (PLoS ONE, 2014)
DNA methylation in plants targets cytosines in three sequence contexts, CG, CHG and CHH (H representing A, C or T). Each of these patterns has traditionally been associated with distinct DNA methylation pathways with CHH methylation being controlled by the RNA dependent DNA methylation (RdDM) pathway employing small RNAs as a guide for the de novo DOMAINS REARRANGED METHYLTRANSFERASE (DRM2), and maintenance DNA METHYLTRANSFERASE1 (MET1) being responsible for faithful propagation of CG methylation. Here we report an unusual 'dense methylation' pattern under the control of MET1, with methylation in all three sequence contexts. We identified epi-alleles of dense methylation at a non coding RNA locus (At4g15242) in Arabidopsis ecotypes, with distinct dense methylation and expression characteristics, which are stably maintained and transmitted in genetic crosses and which can be heritably altered by depletion of MET1. This suggests that, in addition to its classical CG maintenance function, at certain loci MET1 plays a role in creating transcriptional diversity based on the generation of independent epi-alleles. Database inspection identified several other loci with MET1-dependent dense methylation patterns. Arabidopsis ecotypes contain distinct epi-alleles of these loci with expression patterns that inversely correlate with methylation density, predominantly within the transcribed region. In Arabidopsis, dense methylation appears to be an exception as it is only found at a small number of loci. Its presence does, however, highlight the potential for MET1 as a contributor to epigenetic diversity, and it will be interesting to investigate the representation of dense methylation in other plant species.